Synthesis and structural characterization of modified LiMnPO4 cathode materials for lithium ion batteries / Rajammal Karuppiah - Rajammal, Karuppiah (2016)
Rechargeable lithium ion batteries are favorable option for portable electronic devices, electric vehicles and hybrid electric vehicles. Attractive factors such as high energy density, long cycle life and environment friendliness are the main inspirations to make lithium ion batteries as the best choice for energy storage systems. Cathode materials play important role in determining performance of lithium ion batteries. Lithium manganese phosphate, LiMnPO4 is one of the promising cathode materials due to its high energy capacity, non-hazardous, cheap and better chemical and thermal stability. However, poor electronic and ionic conductivities, Jahn-Teller distortion involving Mn3+ ions and larger interface strain due to the volume change between LiMnPO4 and MnPO4 during lithiation and delithiation found to be major drawbacks of its applications. In order to overcome such downsides, various strategies have been carried out as following: (a) particle size reduction and morphology control to improve Li+ diffusion, (b) metal oxide coating to enhance electronic conductivity (c) cation substitution to raise Li+ ions diffusion. In this work, different modifications were approached to study improved electrochemical activity of LiMnPO4. LiMnPO4 cathode materials were prepared by sol gel method with the aid of oxalic acid and effects of different sintering temperatures on structural and electrochemical characterizations were studied. The calcination temperatures have high impact on structural and electrochemical properties. The obtained LiMnPO4 at 700 °C (calcination temperatures) has smaller crystallite size and low strain value than that of other samples. It exhibited superior electrochemical performance among the samples. It delivered initial discharge capacity of 103.4 mAhg-1 at 0.05 C. Apart from that, sodium was substituted partially to lithium site of LiMnPO4. Li0.97Na0.03MnPO4 sintered at 600°C and 700°C delivered discharge capacities of 87.74 mAh g-1 and 99.83 mAh g-1at the 60th cycle which shows capacity retention of 81.23 % and 84.15 % correspondingly. While ZnO coating with different weight percentages were applied on LiMnPO4 to observe the improvement. Galvanostatic charge-discharge tests showed that the ZnO coated LiMnPO4 sample has an enhanced electrochemical performance compared to pristine LiMnPO4. The 2 wt.% of ZnO based LiMnPO4 exhibited maximum discharge capacity of 102.2 mAh g-1 than that of pristine LiMnPO4 (86.2 mAh g-1) and 1wt.% of ZnO based LiMnPO4 (96.3 mAh g-1) respectively. The maximum cyclic stability of 96.3 % was observed in 2 wt.% of ZnO based LiMnPO4 up to 100 cycles. Another modification with aluminium and copper co-doping was made into LiMnPO4 structure. The doping of Al and Cu for Mn in LiMnPO4 exhibited lattice shrinkage and improvement of electronic conductivity. LiMn0.8Al0.1Cu0.1PO4 delivered highest discharge capacity of 166 mAhg-1 and LiMn0.9Al0.05Cu0.05PO4 exhibited initial discharge capacity of 152 mAhg-1 at 0.05C. Al, Cu co-doped samples seem favourable candidate for cathode materials at low current rates while ZnO coated samples would be outstanding choice for high current rates. Doping and metal oxide coating can be used together in future work for better electrochemical properties.